Sedimentology and Lithostratigraphy of the Pila Spi Formation in Koi Sanjaq area, NE Iraq; New insight for depositional Environment and Basin Configuration - Al-Mashaikie, Sa’ad Zeki A. Kader; A. Latif, Rusul Mohammed (Iraqi Journal of Science, 2022)
The Pila Spi formation composed of seven lithotypes; carbonates (dolomite anddolomitic limestone), marl, shale/claystone, red argillaceous mudstone, sandstone,carbonate breccias and debris flow, which are arranged in repeated cycles of mixedsiliciclastic-calciturbidites in a range of gravity-flow regime in the Koi Sanjaq area.Sedimentologic and facies evidences suggest developed marine environment for thePila Spi Formation. Facies analysis and associated sedimentary structures includinggraded beddings decide turbidity and gravity flow regime origin of the rocks.Marine environment is supported by the identifying glauconite and fossils types,which is reported here for the first time rather than lagoon environment.The Pila Spi sequences are grouped into four facies associations confirmingdeveloped marine depositional systems, these are (from bottom to top) channeledslumpedfine and mega carbonate breccias, calciturbidites, faulted and slumpcarbonate mega-breccias, slump/slide carbonate mega-breccias facies associationsrespectively.Petrographic analysis of carbonate units of the Pila Spi rocks in Koi Sanjaq areaindicated that they are composed of skeletal grains with subordinate non-skeletalgrains of tuffaceous fragments, chert, chalcedony, volcanic ash, metamorphic anddetrital iron oxides grains, with noticeable grains of glauconite. Varieties of marinefossils are identified includes planktonic bivalves and benthic forams of cool water,which support the deeper marine environment.Microfacies analysis reveals (15) types, these are; green algal boundstone, algalwackestone dolomudstone, algal dolostone/mudstone, framestone-mudstone, smallbenthic foraminiferal wackestone, algal packstone-mudstone, foraminiferalpackstone-mudstone, algal dolostone, fossiliferous grainstone, foraminiferalpackstone, stromatolite framestone, algal boundstone, calci-microbial grainstonepackstone,and large benthic Foraminiferal bioclasts floatstone. These microfaciestypes are grouped in four facies associations representing the depositionalenvironments of the formation, these are; outer shelf, reef, forereef, reef, backreef.